PENGARUH HARGA, KUALITAS PRODUK DAN WOM (WORD OF MOUTH) TERHADAP KEPUASAN KONSUMEN - Upik Aldiana; Setyo Adji; Edi Santoso (ASSET: Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the effect of price, product quality, WOM (word of mouth) on consumer satisfaction on Herbal Soman Products at Yasmaga fm Ponorogo outlets. PT. Soman Indonesia is one of the original pharmaceutical companies in Indonesia, Soman (Sozo Formula Manggata 1) is Herbal Drops Herbal made from ingredients 39 Natural ingredients consisting of fruits, vegetables and also selected spices. The population in this study were consumers of Soman Herbal Products at Yasmaga Radio FM Ponorogo. This study used the Probability Sampling Technique by means of Random Sampling. Samples taken amounted to 80 respondents with the characteristics of consumers who have made a minimum purchase of 2x. The results showed that price, product quality, WOM (word of mouth) had a positive and significant effect on customer satisfaction both simultaneously and partially. While the coefficient of determination shows the value of 53.1%, which means the price, product quality and WOM (word of mouth) contribution to consumer satisfaction is 53.1% and the remaining 46.9% is influenced by other variables not explained in this study.